Once preguntas sobre la relación entre ética y política - Polo Santillán, Miguel Ángel (2018)
Through eleven questions, the author reviews the relationship between ethics and politics. One strong idea of the article is that the State owes its meaning to the “common good”, understood as the protection of human life and dignity. Thus, political praxis should be extended to the participation of civil society, in order to avoid the weaknesses of the representative institutions and strengthen their democratic sense. More political participation of the citizens gives more ethical sense to the political action, it is all about people being responsible for their own lives.